Características de la docencia mejor evaluada por los alumnos en las diferentes áreas de enseñanza universitaria - Álvarez Rojo, Víctor; García Jiménez, Eduardo; Gil Flores, Javier (Revista Española de Pedagogía, 2018)
We have analyzed the educational performance of twenty-five professors of the University of Seville using technical as depth interview and observation. Those teachers are among the best evaluated by theirs students. In this study, we have extracted some essential characteristics on teaching for each teacher. Analysis of multiple correspondences has allowed to structure the characteristics in professional activity of professors very valued by two axesordimensions: one axe is about trajectory and professional activity and another axe is about educational methodology. These dimensions reflect the existence of different models of quality in teaching associated to the different knowledge areas.
FEATURES OF THE UNIVERSITY WAY OF TEACHING BEST VALUED BY STUDENTS IN DIFFERENT KNOWLEDGE AREAS
Keywords: higher education; teaching quality; teaching evalualion; Revista Española de Pedagogía